Perbandingan Konsep Pendidik Berbasis Agama Dan Sekuler Dalam Perspektif Etika Profesi Guru - Hasriani Mursalim; Dina Dwi Asihna Sinaga; Khadijah, Khadijah; St. Nurhayati Ali (Jurnal Sultra Elementary School, 2026)
This study aims to analyze the comparative concepts of religious and secular educators from the perspective of professional ethics for teachers and their relevance in 21st-century education. This study uses a qualitative approach with a literature review method of various contemporary scientific sources and educational policy documents. The results show that the fundamental difference between the two paradigms lies in the source of legitimacy of professional ethics. The religious perspective bases ethics on transcendental values ​​and religious moral teachings, so that teacher professionalism is understood as a spiritual mandate that demands internal integrity and exemplary behavior. In contrast, the secular paradigm places professional ethics on public rationality, human rights, and normative and accountable institutional standards. Differences are also evident in the orientation of educational goals, where the religious approach emphasizes holistic character formation that combines intellectual, moral, and spiritual aspects, while the secular approach focuses on the development of critical thinking, democratic participation, and global readiness. Nevertheless, both approaches have common ground in the importance of integrity, social responsibility, and teacher professionalism. In the context of a pluralistic society and the era of digital disruption, an integrative approach that combines religious values ​​and modern rationality is the most relevant model. This synthesis enables the development of contextual, adaptive, and comprehensive teaching professional ethics to strengthen the quality of national education.